Carbon Emissions Accounting Disclosure: An Empirical Analysis during the Covid-19 Pandemic Period in a Developing Country - Puspita, Maria Entina; Ratmono, Dwi; Tantri, Mitsalina; Julianto, Yohanes; Ridhasyah, Rizki (International Journal of Energy Economics and Policy, 2024)
Carbon emissions accounting disclosure (CEAD) is an interesting research area that is related to the increase in global warming that is being caused by the use of non-renewable energy. However, there has been no research that has tested the disclosure of carbon emissions during the COVID-19 pandemic using a comprehensive model. Apart from that, there is still limited previous research that focuses on developing countries where the use of fossil-based energy has become an important issue at the moment. In this sense, this study aims to contribute to CEAD by analyzing earnings management, corporate governance, and media exposure as determinants of CEAD in Indonesia, a developing country. The sample consists of 244 firm-year manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The test results, using partial least squares-structural equation modeling (PLS-SEM), indicate support for legitimacy theory, namely the view that corporate governance and media exposure have a positive effect on the level of CEAD. Drawn from the COVID-19 pandemic period, the empirical evidence from this study shows that the sample of manufacturing companies tended to carry out income-increasing earnings management and the disclosure of carbon emissions tended to be low.